El discurso ambiental en Colombia: una mirada desde el Análisis Crítico del Discurso - Mónica Pérez-Marín (Chasqui, 2016)
From critical and postcolonial theories, and under the methodology of Critical Discourse Analysis (ACD), this research presents a representation regime analysis (RR) of the environmental discourse in Colombia. The central argument of this article advocates the idea that the RR associated with the figure of protected areas and natural parks are strongly rooted in a colonizing conservationist logic of the wild nature, typical of the United States, which has its origin in eurocentric and anthropocentric structures, in relation with nature; and that evolves over time towards a discourse of the sustainable development, by which the use and control of nature is legitimized by means of transnational or empire capitals.